1980
DOI: 10.1002/j.1552-4604.1980.tb01673.x
|View full text |Cite
|
Sign up to set email alerts
|

Ketazolam and Diazepam in Anxiety: A Controlled Study

Abstract: Ketazolam (both in once-daily and three-times-daily dosing), diazepam, and placebo were compared for effectiveness in relieving anxious symptomatology in a clinical trial conducted with a total of 222 anxious, non-psychotic outpatients. Results indicated that improvement occurred early in treatment, that ketazolam was equally effective in both once-daily and three-times-daily dosing, and that ketazolam was similar in effect to diazepam. Ketazolam (both once-daily and three-times-daily) and diazepam were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 5 publications
1
55
0
1
Order By: Relevance
“…While PK 9084 is poorly established as an anxioselective agent, buspirone has been shown to be efficaceous in several clinical trials (Goldberg & Finnerty, 1979;Goldberg & Finnerty, 1982;Rickels et al, 1982). These results are consistent with the conclusion that anxiety can be treated by modification of non-GABAergic neurotransmission, possibly including 5-hydroxytryptaminergic, noradrenergic and dopaminergic systems (for review, see: Hoehn-Saric, 1982;Braestrup, 1982).…”
Section: Drugssupporting
confidence: 79%
See 1 more Smart Citation
“…While PK 9084 is poorly established as an anxioselective agent, buspirone has been shown to be efficaceous in several clinical trials (Goldberg & Finnerty, 1979;Goldberg & Finnerty, 1982;Rickels et al, 1982). These results are consistent with the conclusion that anxiety can be treated by modification of non-GABAergic neurotransmission, possibly including 5-hydroxytryptaminergic, noradrenergic and dopaminergic systems (for review, see: Hoehn-Saric, 1982;Braestrup, 1982).…”
Section: Drugssupporting
confidence: 79%
“…Buspirone, a piperazinyl pyrimidine, is a non-benzodiazepine receptor ligand with anticonflict activity (Riblet et al, 1982;Geller & Hartmann, 1982). Several clinical trials have confirmed the non-sedative anxiolytic profile of this compound (Goldberg & Finnerty, 1979;Rickels et al, 1982;Newton et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…The 5-HT 1A -agonist buspirone is effective in the treatment of generalized anxiety disorder, as could be shown in some controlled studies. Buspirone was superior to placebo in some studies (Davidson et al 1999;Enkelmann 1991;Pollack et al 1997) and as effective as benzodiazepines (Feighner et al 1982;Jacobson et al 1985;Rickels et al 1982;Ross and Matas 1987;Strand et al 1990). However, it was less effective than venlafaxine (Davidson et al 1999) or hydroxyzine (Lader and Scotto 1998).…”
Section: Generalized Anxiety Disorder (Gad)mentioning
confidence: 99%
“…Buspirone, 8-(4-(4-(2-pyrimidinyl)-1-piperazinyl)-butyl)-8-azaspiro [4,5]-decane-7, 9-dione hydrochloride (Figure 1), has demonstrable anticonflict actions in several species (monkey, rat, pigeon) (Riblet et al, 1982;Weissman et al, 1984;Barrett et al, 1984) and anxiolytic actions in man (Goldberg & Finnerty, 1979;Rickels et al, 1982). However, buspirone appears to lack many of the pharmacological properties (e.g.…”
Section: Introductionmentioning
confidence: 99%